Hölderlin e Celan - Bernhard Böschenstein (Aisthesis, 2012)
Moving from the analysis of Celan’s poem Ich trink Wein, the essay has the pourpose to shed light on the relationship between the poets Friedrich Hölderlin and Paul Celan. The key-thesis of the text consists of the formulation of a fundamental philosophical and poetical resemblance between Hölderlin’s caesura-concept and Celan’s keyword Atemwende.